Alexander to Actium : the Historical Evolution of the Hellenistic Age. - Green, Peter, 1924- (Hellenistic culture and society., 1990)
The Hellenistic Age, the three extraordinary centuries from the death of Alexander in 323 B.C. to Octavian's final defeat of Antony and Cleopatra at the Battle of Actium, has offered a rich and variegated field of exploration for historians, philosophers, economists, and literary critics. Yet few scholars have attempted the daunting task of seeing the period whole, of refracting its achievements and reception through the lens of a single critical mind. Alexander to Actium was conceived and written to fill that gap. In this monumental work, Peter Green-noted scholar, writer, and critic-breaks w.